Fissuroma bambucicola sp. nov. (Aigialaceae, Pleosporales) from Bamboo in Guizhou, China - Feng, Yao; Zhang, Sheng-Nan; Chen, Ya-Ya; Liu, Zuo-Yi (Phytotaxa, 2022)
During an investigation of fungi on bamboos in Guizhou Province of China, a new ascomycete inhabiting decaying bamboo is introduced based on morpho-molecular evidence. Morphologically, our new species is characterized by hemispherical ascomata with slit-like ostiole, trabeculate pseudoparaphyses, obclavate to cylindrical asci, and fusiform, hyaline, 1-septate ascospores, surrounded by a distinctive thin sheath, which fit well with Aigialaceae. The phylogenetic analyses based on a combined LSU, ITS, SSU, and TEF1-α sequence data showed that the new collections are affiliated with the genus Fissuroma and can be recognized as a new species Fissuroma bambusicola. The comprehensive description and notes of F. bambusicola are provided.